Functional instability in non-contact ankle ligament injuries. Issue 5 (1st October 2000) - Rose, Alison; Lee, Robert J; Williams, Rachel M; Thomson, Lindsay C; Forsyth, Anne
Abstract : Objectives —To measure objectively functional standing balance in the acute stages of non-contact ankle sprain, and to compare patients with controls. Methods —A Chattanooga balance machine was used to measure postural stability in patients with acute ankle sprain and uninjured controls over a two week period, in one and two legged stance, with eyes open and closed. Participants also completed the Olerud and Molander questionnaire to provide a subjective measure of ankle function. Results —There was a highly significant improvement in questionnaire scores for the patients during the study period (p<0.0001). Patients appeared to be less stable than controls in all balance tests, although the difference did not reach significance. There was evidence of improvement over time in the number of tests successfully completed on the injured leg in single legged stance with eyes closed (p = 0.043) between visits 1 and 3. Conclusions —The patient group showed a subjective improvement, which supports clinical experience of treating acute ankle injuries. There is some evidence that on average the patient group appeared to be less stable than controls in all balance tests, although the difference did not reach statistical significance, even on the uninjured leg. There is a need to carry out further studies to confirm the results found in this pilot study and to investigate the hypotheses generated. It would be useful to evaluate a simple test that could be used clinically to monitor progress after ankle injury, and also to identify athletes with decreased functional stability, who may be more at risk of sustaining ankle injury.